Isolation and Identification of Lipase-producing Actinobacteria from the Lut Desert of Iran - Samira Abedi-Dolatabadi; Moj Khaleghi; Sedigheh Ghasemzadeh; Azadeh Lohrasbi-Nejad; Arastoo Badoei Delfard (Journal of Genetic Resources)
Lipases are the third category of widely used hydrolytic enzymes that catalyze the hydrolysis of triacylglycerols, glycerol, and free fatty acids. Actinobacteria, which are Gram-positive bacteria, have the largest genome size among bacteria and produce various secondary metabolites, including enzymes. This study aimed to isolate lipase-producing Actinobacteria strains from the Lut Desert in Iran. In this study, microbial samples isolated from the Lut Desert region of Iran in 2017-2018 were cultured on specific Actinobacteria growth media. These samples were activated and cultivated on Tween 80 agar plates for lipase production. After seven days of bacterial growth, the samples were assessed based on the transparent clear zone diameter around the colonies. The lipase activity was measured spectrophotometrically using para-nitrophenyl palmitate as the specific substrate, and the best lipase-producing strain was identified based on its 16S rRNA sequence. Among the six isolated Actinobacteria strains, three strains exhibited lipase production capability. Strain Ga7 had the largest clear zone with a diameter of 7 mm and lipase activity of 5.45×10 -7 µmol/min, making it the most promising potential lipase producer. Based on its 16S rRNA sequence, strain Ga7 belongs to the genus Streptomyces sp., with 99% similarity to Streptomyces indoligenes. This study highlights the significance of using bacteria as a microbial source for lipase production for future industrial and biotechnological applications. Based on the findings of this study, it was determined that the Ga7 strain, due to its bacterial genus and its isolation from the Gandom Beryan area of the Lut Desert as the hottest place on earth, can be a suitable candidate for lipase production in various industries. These findings emphasize the importance of studying microorganisms from extreme environments like the Lut Desert as rich sources for discovering and utilizing industrial enzymes.